Phishing for solutions. - Neville-Neil, George (New York ACM, 2006)
A koder with attitude, KV answers your questions. Miss Manners he ain't.
Keywords: General Literature; Miscellaneous; Computing Milieux; Computers and society; Electronic commerce; Security; Management of Computing and Information Systems; Security and protection